Handbook of clinical neuropsychology - Gurd, Jennifer M.; Kischka, Udo.; Marshall, John C. (Oxford : Oxford University Press, 2010)
Clinical neuropsychology remains one of the fastest growing specialities within clinical psychology, neurology, and the psychiatric disciplines. This second edition provides a practical guide for those interested in the professional application of neuropsychological approaches and techniques in clinical practice.
Previous ed.: 2003.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Clinical neuropsychology